К теории групп с обобщенным условием минимальности для замкнутых подгрупп - Чарин, В.С. (Український математичний журнал, 1999)
Доведено, що топологічна абелева локально компактна група з узагальненою умовою мінімальності для замкнених підгруп є групою одного з наступних типів: 1) група з умовою мінімальності для замкнених підгруп; 2) адитивна група Jр — кільця цілих р-адичних чисел; 3) адитивна група Rp поля p-адичних чисел (p — просте число). We prove that a topological Abelian locally compact group with generalized minimality condition for closed subgroups is a group of one of the following types: 1) a group with minimality condition for closed subgroups, 2) an additive group of theJ p -ring of integerp-adic numbers, 3) an additive groupR p of the field ofp-adic numbers (p is a prime number).